Sous les yeux de l’Occident : recherches féministes et discours coloniaux - Mohanty, Chandra Talpade (Genre, postcolonialisme et diversité de mouvements de femmes, 2010)
Note de l’éditeur Traduit de l’anglais. Texte original: Under Western eyes : Feminist scholarship and colonial discourses. In Feminism without borders : Decolonizing theory, practicing solidarity. 17-42. Durham : Duke University Press. 2003. Tous droits réservés. Reproduit avec l’aimable autorisation de l’éditeur. Parution originale 1986.
Keywords: EDI; afro-féminisme; approches et analyses; cours; discipline; discours dominant; droits des femmes*; ethnocentrisme; féminisme africain; féminisme autochtone; féminisme du sud; féminisme décolonial; féminisme transnational; histoire et politique; injustices épistémiques; inégalités; justice sociale; militance; patriarcat; phi4336; philosophie politique; pol4212; pratiques féministes; premier cycle; privilèges; racisme; sciences humaines; sociologie; sujet du féminisme; système colonial; systèmes d'oppressions; thématiques; théorie féministe; violences

Queer Theory and Native Studies: The Heteronormativity of Settler Colonialism - Smith, A. (GLQ -NEW YORK-, 2010)
Queer studies highlights the importance of developing analyses that go beyond identity and representational politics. For Native studies in particular, queer theory points to the possibility of going beyond representing the voices of Native peoples, a project that can quickly become co-opted into providing Native commodities for consumption in the multicultural academic-industrial complex. The subjectless critique of queer theory can assist Native studies in critically interrogating how it could unwittingly re-create colonial hierarchies even within projects of decolonization. This critique also sheds light on how Native peoples function within the colonial imaginary-including the colonial imaginary of scholars and movements that claim to be radical. At the same time, Native studies can build on queer of color critique's engagement with subjectless critique. In the move to go "postidentity," queer theory often reinstantiates a white supremacist, settler colonialism by disappearing the indigenous peoples colonized in this land who become the foils for the emergence of postcolonial, postmodern, diasporic, and queer subjects. With respect to Native studies, even queer of color critique does not necessarily mark how identities are shaped by settler colonialism. Thus a conversation between Native studies and queer theory is important, because the logics of settler colonialism and decolonization must be queered in order to properly speak to the genocidal present that not only continues to disappear indigenous peoples but reinforces the structures of white supremacy, settler colonialism, and heteropatriarchy that affect all peoples.
Keywords: amériques; approches et analyses; colonialisme; communication; cours; discipline; féminisme autochtone; féminisme décolonial; histoire et politique; militance; premier cycle; queer; régions géographiques; sciences humaines; soc2014; suprématie blanche; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études culturelles